2013
DOI: 10.1194/jlr.m038281
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myeloperoxidase decreases vascular oxidative stress and increases vasodilatation in sickle cell disease mice

Abstract: Although polymorphonuclear neutrophils (PMN) are well recognized for playing important roles in infl ammation in sickle cell disease (SCD), direct evidence linking myeloperoxidase (MPO) to impaired vascular endothelial cell (EC) function in SCD remains lacking. Over the last 25 years, only a handful of studies have been published suggesting that MPO may be involved. One of the fi rst reports, published in 1986, showed that vaso-occlusive crises increased PMN stickiness, an index of activation, in SCD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 17 publications
6
37
0
Order By: Relevance
“…Of importance, we have demonstrated that KYC “competitively inhibits” MPO by outcompeting MPO substrates such as Cl − for the active site and in so doing accelerates H 2 O 2 consumption (Zhang et al 2013a). The importance of this property is underscored by our report showing that KYC decreased the accumulation of MPO in aortas isolated from sickle cell mice to the same levels as control mice (Zhang et al 2013b). In addition, KYC increased endothelial cell-dependent vasodilation in sickle cell mice by nearly 2-fold to ~60% of control levels (Zhang et al 2013b).…”
Section: Discussionmentioning
confidence: 90%
“…Of importance, we have demonstrated that KYC “competitively inhibits” MPO by outcompeting MPO substrates such as Cl − for the active site and in so doing accelerates H 2 O 2 consumption (Zhang et al 2013a). The importance of this property is underscored by our report showing that KYC decreased the accumulation of MPO in aortas isolated from sickle cell mice to the same levels as control mice (Zhang et al 2013b). In addition, KYC increased endothelial cell-dependent vasodilation in sickle cell mice by nearly 2-fold to ~60% of control levels (Zhang et al 2013b).…”
Section: Discussionmentioning
confidence: 90%
“…SCA is associated with increased oxidative stress, neutrophil leucocytosis and vascular endothelial dysfunction, all of which are also associated with increased PS exposure (Jain, 1985; Hebbel, 1991; Kuypers, 1998; Mutze et al , 2003; Banerjee & Kuypers, 2004; Zhang et al , 2013). Recent reviews have reinforced the view that ROS are actively involved in lipid scrambling in SCA (Cimen, 2008; Mohanty et al , 2014; Voskou et al , 2015), with limited experimental evidence supporting this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly significant in diseases such as SCA in which vascular oxidative stress is increased (Rice‐Evans et al , 1986) with accumulations of highly reactive oxygen species (ROS) including the superoxide anion, hydrogen peroxide and the hydroxyl radical (Sies, 1997; Chirico & Pialoux, 2012; Voskou et al , 2015). Myeloperoxidase released from activated neutrophils may also add to oxidant challenge in SCA, through production of hypochlorous acid (HOCl) from hydrogen peroxide (Vissers et al , 1994; Mutze et al , 2003; Zhang et al , 2013). Thiol oxidation has also been associated with both inhibition of the flippase and stimulation of the scramblase (Morrot et al , 1989; Connor & Schroit, 1990; Devaux & Zachowski, 1994; Martin & Jesty, 1995; de Jong & Kuypers, 2006).…”
mentioning
confidence: 99%
“…3‐Cl‐tyr levels were evaluated by Western blot. After blotting for 3‐chlorotyrosine, 3 immunospecific bands of molecular weight 43, 55, and 72 kDa were visualized 15, 16…”
Section: Methodsmentioning
confidence: 99%